A new species of the artiopodan arthropod Acanthomeridion from the lower Cambrian Chengjiang Lagerstätte, China, and the phylogenetic significance of the genus. (2nd September 2017) - Hou, Xianguang; Williams, Mark; Gabbott, Sarah; Siveter, David J.; Siveter, Derek J.; Cong, Peiyun; Ma, Xiaoya; Sansom, Robert
Abstract : New material of the rare arthropod Acanthomeridion, including Acanthomeridion anacanthus sp. nov., is described from the lower Cambrian Chengjiang biota, Yunnan Province, China. The material includes a specimen with paired gut diverticulae along the length of the mid-gut that resemble structures in other artiopodan arthropods such as naraoiids. Previous phylogenetic analyses have indicated a petalopleuran/xandarellid affinity for Acanthomeridion, but our analysis resolves Acanthomeridion outside the main subclades of the Artiopoda (Aglaspidida + Trilobita, Nektaspida, Cheloniellida + Xenopoda, Conciliterga, Petalopleura (including Xandarellida)) as the most basal artiopodan. http://zoobank.org/urn:lsid:zoobank.org:pub:3563C327-EF9C-4A49-B200-417CE5D95D60